Cytokine responsiveness of CD8+ T cells is a reproducible biomarker for the clinical efficacy of dendritic cell vaccination in glioblastoma patients. Issue 1 (13th May 2014) - Everson, Richard G; Jin, Richard M; Wang, Xiaoyan; Safaee, Michael; Scharnweber, Rudi; Lisiero, Dominique N; Soto, Horacio; Liau, Linda M; Prins, Robert M
Abstract : Background: Immunotherapeutic approaches, such as dendritic cell (DC) vaccination, have emerged as promising strategies in the treatment of glioblastoma. Despite their promise, however, the absence of objective biomarkers and/or immunological monitoring techniques to assess the clinical efficacy of immunotherapy still remains a primary limitation. To address this, we sought to identify a functional biomarker for anti-tumor immune responsiveness associated with extended survival in glioblastoma patients undergoing DC vaccination. Methods: 28 patients were enrolled and treated in two different Phase 1 DC vaccination clinical trials at UCLA. To assess the anti-tumor immune response elicited by therapy, we studied the functional responsiveness of pre- and post-vaccination peripheral blood lymphocytes (PBLs) to the immunostimulatory cytokines interferon-gamma (IFN-γ) and interleukin-2 (IL-2) in 21 of these patients for whom we had adequate material. Immune responsiveness was quantified by measuring downstream phosphorylation events of the transcription factors, STAT-1 and STAT-5, via phospho-specific flow cytometry. Results: DC vaccination induced a significant decrease in the half-maximal concentration (EC-50) of IL-2 required to upregulate pSTAT-5 specifically in CD3 + CD8 + T lymphocytes (p < 0.045). Extended survival was also associated with an increased per cell phosphorylation of STAT-5 in cytotoxic T-cells following IL-2 stimulation when the median post/pre pSTAT-5 ratio was used to dichotomize the patients (p = 0.0015, log-rank survival; hazard ratio = 0.1834, p = 0.018). Patients whose survival was longer than two years had a significantly greater pSTAT-5 ratio (p = 0.015), but, contrary to our expectations, a significantly lower pSTAT-1 ratio (p = 0.038). Conclusions: Our results suggest that monitoring the pSTAT signaling changes in PBL may provide a functional immune monitoring measure predictive of clinical efficacy in DC-vaccinated patients.